Revolutionary movements in Africa : an untold story - Bianchini, Pascal; Sylla, Ndongo Samba; Zeilig, Leo (Las Vegas ; London : Pluto Press, 2024)
While the revolutionary leftist movements of the 1960s and'70s in Europe, the United States and Latin America have been the subject of abundant literature, similar movements that emerged in Africa have received comparatively very little attention. This book sheds new light on these political movements. Africa's left were extremely active in these years. With pro-Soviet movements, Maoism, Trotskyism, Guevarism, Pan-Africanism and the Black Panthers, the rumble of revolution was felt across the continent. From feminist student rebels in Nigeria to pro-democracy moments in Liberia, the exciting and complex interplay between these many actors changed Africa forever. Can we see echoes of these movements in African politics today? What can we learn from the people who lived through these decades? This unique collection will open the eyes of leftists across the world who will find new and important insights into an important chapter in global history.
Cover -- Title -- Copyright -- Contents -- About Codesria -- Introduction: Remembering a Forgotten History -- 1. Political Struggle in Senegal in the 1960s and 1970s: The Artistic and Literary Front -- 2. The Revolutionary Left in Sub-Saharan Africa: The Case of Mali -- 3. The History of the Upper Volta Revolutionary Left: From Ideological Struggles within the Student Movement to the Creation of the PCRV and the ULC -- 4. Student and 'Post'-Student Activism in Niger, 1970s-80s -- 5. The Labour Movement, Marxism, Northern Leftists, Feminist Socialism and Student Rebels in Nigeria, 1963-78 -- 6. The Movement for Justice in Africa and Democratisation in Liberia -- 7. The Frolinat and the Saharan Footprint on an African Revolution: The Case of the Chadian North -- 8. Brazzaville: Crossroads of the Revolutionary Left in Central Africa in the 1960s and 1970s -- 9. May 1972 in Madagascar: A Student Movement Causing the Fall of the 'Father of Independence' -- 10. Southern Sudanese Radical Projects, c. 1963-83 -- 11. Communists of Katwe: Pan-African Marxism and the Uganda People's Congress, c. 1960-c. 1964 -- 12. Challenging 'African Socialism' through Marxism-Leninism: The University Students African Revolutionary Front in Tanzania -- 13. Questions from the Dar es Salaam Debates -- 14. The Road to Durban: Workers' Struggles, Student Movements, and the Resurgence of Resistance Politics in Namibia and South Africa -- 15. Dimitri Tsafendas: An African Revolutionary -- Conclusion: A Tribute to Two 'Great Witnesses' Invited to the Dakar Conference in 2019, Moctar Fofana Niang and Euǧnie Rokhaya Aw -- Notes on Contributors -- Index.
Includes index
eBooks on EBSCOhost
Keywords: Revolutions -- Africa; Africa -- Politics and government; Révolutions -- Afrique; Afrique -- Politique et gouvernement; Politics and government; Revolutions; Africa